Give me the banjo [videorecording (DVD)] - Fields, Marc; Martin, Steve, 1945-; Seeger, Pete, 1919-2014; Scruggs, Earl; Fleck, Béla, 1958- (Docuramafilms : Distributed by New Video, 2012)
The banjo has been an emblem of American culture for centuries, yet few realize the instrument's complicated, checkered past. Narrated by Steve Martin and featuring such banjo masters as Pete Seeger, Earl Scruggs and Bela Fleck, goes beyond the stereotypes and delves into the musical odyssey of the banjo, from its African roots to the present day.